The Pathophysiological Role of Neutrophil Extracellular Traps in Inflammatory Diseases - Bonaventura, Aldo; Liberale, Luca; Carbone, Federico; Vecchié, Alessandra; Diaz-Cañestro, Candela; Camici, Giovanni G.; Montecucco, Fabrizio; Dallegri, Franco (Thrombosis and Haemostasis, 2018)
Neutrophil pathogen-killing mechanism termed neutrophil extracellular traps (NETs) has been recently identified. NETs consist of chromatin and histones along with serine proteases and myeloperoxidase and are induced by a great variety of infectious and non-infectious stimuli. NETosis is a kind of programmed neutrophil death characterized by chromatin decondensation and release of nuclear granular contents, mainly driven by peptidylarginine deiminase 4 citrullination of histones. Although classically related to the protection against infectious pathogens, nowadays NETs have been described as a player of several pathophysiological processes. Neutrophil dysregulation has been demonstrated in the pathogenesis of most representative vascular diseases, such as acute coronary syndrome, stroke and venous thrombosis. Indeed, NETs have been identified within atherosclerotic lesions and arterial thrombi in both human beings and animal models. Moreover, an imbalance in this mechanism has been proposed as a critical source of modified and/or externalized autoantigens in autoimmune and inflammatory diseases. Finally, an update on the role of NETs in the pathogenesis of cancer has been included. In the present review, based on papers released on PubMed and MEDLINE up to July 2017, we point to update the knowledge on NETs, from their structure to their roles in infectious diseases as well as in cardiovascular diseases, autoimmunity, metabolic disorders and cancer, with a look to future perspectives and therapeutic opportunities.
Keywords: NETs; infectious diseases; autoimmune diseases; metabolic disorders; cancer